Socioeconomic impact of restless legs syndrome and inadequate restless legs syndrome management across European settings. (25th November 2020) - Trenkwalder, C.; Tinelli, M.; Sakkas, G. K.; Dauvilliers, Y.; Ferri, R.; Rijsman, R.; Oertel, W.; Jaarsma, J.
Abstract : Restless legs syndrome (RLS) is one of the most common neurological disorders. It describes an irresistible urge to move the legs, mostly manifested in the evening and at night, which can lead to severe sleep disturbance. As part of the European Brain Council (EBC)‐led Value‐of‐Treatment project, this study aimed at capturing the socioeconomic impact of RLS related to the inadequate diagnosis and treatment across different European healthcare settings. The economic burden of RLS was estimated using the published EBC framework of analysis in three separate European Union healthcare systems (France, Germany, and Italy). The RLS care pathway was mapped to identify the unmet needs of patients. Based on specific patient stories, the economic impact of correctly diagnosing RLS and changing between inadequate and target treatment was calculated using appropriate scenario analysis. RLS proved to be a significant personal and social burden, when epidemiological data, high prevalence of RLS, and its need for treatment are combined. By looking at the savings emerging from the provision of optimal care management (timely and correct diagnosis, evidence‐based therapy, avoidance of therapy‐related complications such as augmentation), the authors foresee substantial economic savings with the achievement of adequate diagnosis and treatment of RLS. Education about RLS is urgently needed for all subspecialties involved in RLS patient care as well as the general public. Equally important, the search for new causal treatment strategies should be intensified to reduce suffering and substantial societal cost. Abstract : As part of the European Brain Council (EBC)‐led Value‐of‐Treatment (VoT) Project, this study aimed at capturing the socio‐economic impact of RLS related to the inadequate diagnosis and treatment across different European healthcare settings. RLS proved to be a significant personal and social burden, when including epidemiological data and high prevalence of RLS and its need for treatment. By looking at the savings emerging from the provision of optimal care management, the authors foresee substantial economic savings with the achievement of adequate diagnosis and treatment of RLS.